2022
DOI: 10.1101/2022.10.09.508561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GABA decrease is associated with degraded neural specificity in the visual cortex of glaucoma patients

Abstract: Glaucoma is an age-related neurodegenerative disease of the visual system, affecting both the eye and the brain. Yet its underlying metabolic mechanisms and neurobehavioral relevance remain largely unclear. Here, using proton magnetic resonance spectroscopy and functional magnetic resonance imaging, we investigated the GABAergic and glutamatergic systems in the visual cortex of glaucoma patients, as well as neural specificity, which is shaped by GABA and glutamate signals and underlies efficient sensory and co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated the role of (gamma-aminobutyric acid) GABA+ in inhibitory control, while glutamate/glutamine (Glx) primarily affects excitatory control, thereby contributing to the balance between inhibition and excitation (known as the I-E balance). A recent study showed that both GABA and glutamate level was associated with glaucoma severity and targeting GABA could possibly enhance the neural speci city in visual cortex [57]. To obtain accurate metabolic concentrations, the MEGA-PRESS sequence will be used to calculate GABA+ values, and the PRESS sequence will be used to measure Glx levels.…”
Section: ) Quality Of Life (Qol)mentioning
confidence: 99%
“…Previous research has demonstrated the role of (gamma-aminobutyric acid) GABA+ in inhibitory control, while glutamate/glutamine (Glx) primarily affects excitatory control, thereby contributing to the balance between inhibition and excitation (known as the I-E balance). A recent study showed that both GABA and glutamate level was associated with glaucoma severity and targeting GABA could possibly enhance the neural speci city in visual cortex [57]. To obtain accurate metabolic concentrations, the MEGA-PRESS sequence will be used to calculate GABA+ values, and the PRESS sequence will be used to measure Glx levels.…”
Section: ) Quality Of Life (Qol)mentioning
confidence: 99%